Antibiotic delivery evaluation against Mycobacterium fortuitum using nanofluids containing carbon nanotubes - Hamid Naderi Pargami; Seyed Davar Siadat; Vahid Amiri; Mojgan Sheikhpour (BMC Microbiology, 2022)
Abstract Background Mycobacterium fortuitum (M. fortuitum) is a bacterium, which can cause infections in many anatomical regions of the body, including the skin, lymph nodes, and joints. This bacterium, which belongs to a group of bacteria known as nontuberculous mycobacteria, is regarded as an important nosocomial pathogen worldwide owing to its increasing antibiotic resistance. Recently, the antimicrobial effects of carbon nanotubes have been reported in numerous studies. These nanotubes can be very useful in drug delivery; besides, they exhibit unique properties against multidrug-resistant bacterial infections. This study aimed to investigate the antimicrobial effects of carboxyl-functionalized multi-walled carbon nanotubes (MWCNT-COOH) to reduce antibiotic resistance. Methods In this study, antibacterial effects of nanofluids containing functionalized MWCNTs at initial concentration of 2 mg/mL and serial dilutions of 54, 28.5, 14.25, 7.12, 3.5 µg/mL, antibiotics alone and combination of nanofluids with antibiotics were investigated. Standard and resistant strains of M. fortuitum were obtained from the microbial bank of the Department of Mycobacteriology and Pulmonary Research, Pasteur Institute of Iran. Results It was observed that nanofluid containing MWCNT-COOH can exert antimicrobial effects on M. fortuitum and significantly reduce bacterial resistance to antibiotics including kanamycin and streptomycin. In the presence of antibiotics and nanofluids containing MWCNT-COOH at a dose of 28.5 µg/mL, no growth was observed. Conclusion One of the main antimicrobial mechanisms of MWCNT-COOH is penetration into the bacterial cell wall. In this study, by using the nanofluid containing MWCNT-COOH with increased stability, the antibiotic resistance of M. fortuitum was significantly reduced at lower dilutions compared to the antibiotic alone.